1991
DOI: 10.1002/j.1460-2075.1991.tb08025.x
|View full text |Cite
|
Sign up to set email alerts
|

Epstein Barr virus/complement C3d receptor is an interferon alpha receptor.

Abstract: Interferon alpha contains a sequence motif similar to the complement receptor type two (CR2/CD21) binding site on complement fragment C3d. Antibodies against a peptide with the CR2 binding sequence on C3d react with a peptide carrying the IFN alpha CR2 binding motif (residues 92–99) and with recombinant IFN alpha. The IFN alpha‐derived peptide, as well as recombinant IFN alpha, inhibits C3bi/C3d interaction with CR2 on the Burkitt lymphoma Raji. The direct interaction of IFN alpha and CR2 is inhibited by polyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(67 citation statements)
references
References 50 publications
1
66
0
Order By: Relevance
“…The extracellular part of the CD21 molecule consists of 15 or 16 SCR domains [1]. The binding sites for C3d, EBV and IFN-a are all localized in the first two SCR [1,3]. A deletion of this region would presumably lead to a CD21 molecule unable to bind EBV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracellular part of the CD21 molecule consists of 15 or 16 SCR domains [1]. The binding sites for C3d, EBV and IFN-a are all localized in the first two SCR [1,3]. A deletion of this region would presumably lead to a CD21 molecule unable to bind EBV.…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, it consists of 15 or 16 extracellular short consensus repeats (SCR) followed by a transmembrane domain and an intracytoplasmic region [1]. CD21 was described as a receptor for the envelope glycoprotein gp350/ 220 of the EBV [2] and also as a receptor for interferon-alpha (IFN-a) [3]. It is found on mature B lymphocytes and follicular dendritic cells [1].…”
Section: Introductionmentioning
confidence: 99%
“…It also acts as a cellular receptor for Epstein-Barr virus (EBV) [7,8] and interferon c~ (c~-IFN) [9]. It can be phosphorylated following interaction with its ligands [10,11] and it is involved in important immunoregulatory processes, including *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the C3d homologous regions described on different CR2 ligands (~-IFN, EBV) [9,27,28] have been considered in the CR2 function. However, little is known about the expression of anti-C3d reactive binding sites (hereafter referred as C3d determinants) on CR2 or on proteins of CR2 positive cells, even if it is demonstrated that anti-C3D antibody inhibits the binding of c~-IFN to CR2 [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation